Specifying Knee Joint Angle (90) For Different Limb Heights And Its Effect On Oxygenic Power In Standardized Harvard's Test - Noureddine, Samah (Journal of Physical Education, 2011)
The aim of the study is to identify different height platform according to knee joint angle (90) using different leg heights. It also aims at identifying the percentage of limb height contribution in oxygenic power as well as identifying the effect of specifying knee joint angle using different limb height on the oxygenic power in Harvard's standardized test. The researcher used the descriptive method. The subjects were 502 students from the college of physical education for the academic year 2009 – 2010. The researcher concluded that specifying knee joint angle using different leg highest play an important role in specifying the height of the platform and contribution percentage in Harvard's standardized test. She also concluded that specifying knee joint angle using different leg heights in this test had a positive effect on oxygenic power. Finally the researcher recommended stressing the use of Harvard's standardized test according to the accurate adjustments during measuring oxygenic power